2012
DOI: 10.3945/jn.112.159830
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Gastric Sieving by Blending a Solid/Water Meal Enhances Satiation in Healthy Humans

Abstract: Separation of solids and liquids within the stomach allows faster gastric emptying of liquids compared with solids, a phenomenon known as sieving. We tested the hypothesis that blending a solid and water meal would abolish sieving, preventing the early rapid decrease in gastric volume and thereby enhancing satiety. We carried out 2 separate studies. Study 1 was a 2-way, crossover, satiety study of 22 healthy volunteers who consumed roasted chicken and vegetables with a glass of water (1008 kJ) or the same blen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 28 publications
4
70
1
Order By: Relevance
“…The active meal had a gastric retention half-time 30 min longer than the control meal. Although this seems to be in disagreement with a study showing that a mixed solid/liquid food empties faster and is less satiating than the same meal after homogenization to a "soup" (22), in that case the authors suggested that the mixed solid/liquid system initially emptied the liquid portion, which had a low energy density and in this way more quickly reduced the gastric volume and hence the sensation of fullness. Another study demonstrated faster gastric emptying when the viscosity of a meal was increased by adding pectin (30).…”
Section: Discussionmentioning
confidence: 89%
“…The active meal had a gastric retention half-time 30 min longer than the control meal. Although this seems to be in disagreement with a study showing that a mixed solid/liquid food empties faster and is less satiating than the same meal after homogenization to a "soup" (22), in that case the authors suggested that the mixed solid/liquid system initially emptied the liquid portion, which had a low energy density and in this way more quickly reduced the gastric volume and hence the sensation of fullness. Another study demonstrated faster gastric emptying when the viscosity of a meal was increased by adding pectin (30).…”
Section: Discussionmentioning
confidence: 89%
“…It is known that gastric sieving of water occurs, which can be mitigated by blending the water with the stimulus (26). The blending of a stimulus may influence both the energy load sensed in the duodenal of the emptied gastric content as well as the viscosity of the content in the stomach.…”
Section: Ad Libitum Intakementioning
confidence: 99%
“…The use of advanced imaging technologies has recently demonstrated how the physical properties of the meal can modulate satiety and the rate of nutrient delivery to the small bowel, by simply modifying the intragastric distribution of the meal (Boulby et al, 1999;Faas et al, 2002;Kunz et al, 2005;Marciani et al, 2001Marciani et al, , 2007Marciani et al, , 2012. However, up to now little is known about the mechanisms underpinning the distribution and mixing of different digesta systems within the stomach.…”
Section: Introductionmentioning
confidence: 97%